2018
DOI: 10.1007/s10797-018-9484-5
|View full text |Cite
|
Sign up to set email alerts
|

Distributional and revenue effects of a tax shift from labor to property

Abstract: Contrary to frequent recommendations of the public finance literature and international institutions, a persistently high tax wedge on labor is observed in Europe. Simultaneously, the scope for shifting taxes to more growth-friendly revenue sources appears underused. This motivates our simulation of a tax shift from labor to property for Germany, a country where property tax revenues are particularly low and the tax wedge on labor income is among the highest in industrialized countries. We simulate a reform wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Both Figari et al . () and Paetzold and Tiefenbacher () include simulations of revenue‐neutral scenarios. In the countries analyzed in Figari et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Figari et al . () and Paetzold and Tiefenbacher () include simulations of revenue‐neutral scenarios. In the countries analyzed in Figari et al .…”
Section: Resultsmentioning
confidence: 99%
“…(), a tax rate reduction leads to gains only in the upper quintile, while a general increase in tax exemption increases the disposable income of the lower/middle quintiles. Paetzold and Tiefenbacher () find that the largest gains from a housing‐tax reform accrue to the upper middle deciles when revenue is spent on a proportionate reduction of the social insurance contribution. When revenue is instead spent on a lump‐sum rebate on the social insurance contribution, the lower middle deciles show the largest gains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, property taxes are relatively low in Germany, accounting for about 0.44% of GDP in 2010, significantly lower than in most of the EU (Paetzold and Tiefenbacher (2018)). There are two types of property tax, Property Tax A (for agricultural properties) and Property Tax B (for everything else).…”
Section: B2 Taxesmentioning
confidence: 91%
“…The switch to taxation, based on the real estate value, tends to be recommended for countries having low real estate tax incomes. For example, Paetzold and Tiefenbacher (2018) performed a simulation of real estate taxation according to market value in Germany with regard to the possibility of switching from labor taxation to real estate taxation since such income is low in Germany. They found that the revised tax base would allow a significant reduction in the implicit tax rate for work.…”
Section: Introductionmentioning
confidence: 99%